THE IMPACT OF THE ENGLISH LANGUAGE ON GLOBAL BUSINESS AND ECONOMICS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The English language has become an essential instrument in global business and economic development. Its pervasive use facilitates communication among multinational corporations, simplifies international trade processes, and enhances investment opportunities across borders. This paper examines the influence of English on global economic activities, focusing on its role in fostering business efficiency, market expansion, and competitive advantage. The study adopts a qualitative approach by analyzing contemporary trends, corporate practices, and statistical data related to English usage in commerce. The findings indicate that proficiency in English is strongly correlated with improved negotiation outcomes, broader access to international markets, and enhanced professional mobility. The discussion highlights the strategic importance of English language skills in maintaining economic competitiveness and sustaining growth in the globalized business environment.